McGrath, Kate. Royal Rage and the Construction of Anglo-Norman Authority, c. 1000-1250 - Sofia FAGIOLO (Studia Historica. Historia Medieval, 2020)
Recensión del libro de K. McGrath intitulado "Royal Rage and the Construction of Anglo-Norman Authority, c. 1000-1250", publicado en 2019.